An approach to design feedback controllers for flight control systems employing the concepts of gain scheduling and optimization. - Alex Sander Ferreira da Silva (2009)
The role of feedback in the design of aircraft stability and control is becoming increasingly important. The basic reason driving this trend is the necessity to cope with a growing number of more stringent requirements, which are sometimes conflicting. This work presents a design methodology applicable to flight control laws, which can be either a control and stability augmentation system (CSAS) or an automatic flight control system (AFCS). A key feature of the proposed method is the definition of a simple cost function, which incorporates both performance and robustness requirements. The optimization of this cost function is employed to tune some of the control law parameters. It is also presented how to integrate this optimization procedure with the other important design steps, such as requirements definition, data filtering, control law structure definition, shaping the input-output transmission via pre-filters, etc. It is emphasized, at this point, that the format of this cost function is able to encapsulate, in a straightforward manner, the requirements normally applicable to the feedback portion of flight control laws. It is also flexible enough to accommodate different choices of data preprocessing, as well as different choices of feedback structure. The final design step is the setting of appropriate scheduling function for each of the defined scheduled parameters. For illustration purposes, four design examples are presented, namely a yaw damper, a bank angle rate/side slip angle regulator, a pitch attitude rate regulator and a pressure altitude regulator. The aircraft model under consideration is based on available data from Boeing 747. Sensors and actuators dynamics, as well as transport delays due to digital control implementation, are considered. The results show that the proposed methodology is able to satisfactorily fulfill the design requirements normally applicable to flight control laws.